Definição de estabilidade produtiva e relação com atributos de solo em áreas manejadas com agricultura de precisão - Eitelwein, Mateus Tonini (2013)
The mapping of grain yield is the main tool for analysis of the results of the techniques of precision agriculture used. In this sense, the aim of this study was to describe the equipment and clarify the current state of the art mapping yield (Chapter I), to analyze the occurrence of similarity between maps over time using different cultures (Chapter II), and finally, determine the influence that soil properties exert on crop yields (Chapter III). In Chapter I deal with the basic equipment that composes a set of monitoring harvest, giving emphasis on yield sensors on the market, the sequence shows the possibilities of using yield maps for management areas. For analysis of yield stability (Chapter II), there were four areas with a history of monitoring four crops of soybean, corn, wheat and oats. The areas were divided by a regular grid (20 x 20 m) for each raster is assigned the value of average yield of the points that were inside. Data were normalized to enable the temporal analysis. The correlation between soil properties and productivity (Chapter III) was evaluated in an area of 88 acres using the Spearman correlation. The soil samples were taken manually auger at a depth from 0 to 0.1 m, over a regular grid (50 x 50 m). The yield values of these points were determined by averaging the sample points using different radius in three cultures. The results demonstrated the presence of yield stability, especially in areas with large variation in yield in one year. The methodology should be used with caution, especially in places where there is a tendency to homogeneity in yield. The radius sample used to determine the value of yield point has a direct influence on the values of the correlations. Increasing the radius to the sample value of 30 meters provided significant gradual increase in the values of correlations. The phosphorus was the nutrient that showed high positive correlation with yield, despite being above the levels described for the critical state.